2020
DOI: 10.1155/2020/8866041
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Skewed Line Segmentation Technique for Cursive Script OCR

Abstract: Segmentation of cursive text remains the challenging phase in the recognition of text. In OCR systems, the recognition accuracy of text is directly dependent on the quality of segmentation. In cursive text OCR systems, the segmentation of handwritten Urdu language text is a complex task because of the context sensitivity and diagonality of the text. This paper presents a line segmentation algorithm for Urdu handwritten and printed text and subsequently to ligatures. In the proposed technique, the counting pixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The handwritten script is usually written in cursive, even in Latin scripts. Segmenting cursive scripts is more complicated than segmenting printed scripts [31,32]. Handwritten character recognition has essential applications such as sorting postal mail, processing handwritten forms, and processing bank checks [33].…”
Section: Literature Review 21 Printed and Handwritten Ocrmentioning
confidence: 99%
See 1 more Smart Citation
“…The handwritten script is usually written in cursive, even in Latin scripts. Segmenting cursive scripts is more complicated than segmenting printed scripts [31,32]. Handwritten character recognition has essential applications such as sorting postal mail, processing handwritten forms, and processing bank checks [33].…”
Section: Literature Review 21 Printed and Handwritten Ocrmentioning
confidence: 99%
“…Scanned images or images taken from a phone could suffer from the skew problem and positioning the image in the correct direction enhances the recognition rate of the OCR system. Malik et al [32] and Ahmad et al [40] proposed Arabic OCR that corrects the skewness in the input image reported that the skewness correction enhanced the character segmentation. In Fig.…”
Section: Image and Video-based Ocrmentioning
confidence: 99%
“…This dependency also affects the accuracy or Urdu OCR. The proposed Urdu OCR systems 13,28,29,46 which achieve good accuracy are trained on particular font sizes hence their performance decreases on a different font size on which the proposed systems are not trained. The absence of bench mark Urdu OCR corpora also remained a problem for so many years.…”
Section: Ta B L E 1 a Comparison Between The Existing Techniques Of O...mentioning
confidence: 99%
“…ese articles on Manchu character recognition are all based on character segmentation and used manual design to extract shallow features. However, the segmentation-based OCR method is based on accurate character segmentation technology [21]. For historical document images, due to the complexity of various typefaces and styles, inconsistent lighting during image capture, noise caused by capture equipment, and variable background colors (among other idiosyncrasies), correct segmentation of characters becomes more challenging.…”
Section: Manchu Language Ocrmentioning
confidence: 99%